The relationship between organizational commitment and job performance among public employees at Pejabat Tanah Dan Galian Selangor/ Nurul Ain Anuar - Anuar, Nurul Ain (2018)
The objective of this study is to examine the relationship between Organizational Commitment and Job Performance of employees with lower management and middle management staff working in Pejabat Tanah dan Galian, Selangor. It is hypothesized that organizational commitment has a positive influence on job performance. The data collection method in this study using questionnaire survey which been distributed to all 103 staff at Pejabat Tanah dan Galian, Selangor. Results were analyzed with correlation by using Statistical Package for Social Sciences (SPSS) version 23.0. The outcome of this findings shows that organizational commitment has significant relationships with job performance. The study also presents recommendation for future research